Linking farm and fish pond - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The need for new sustainable farming systems has been recognized for a long time. Systems that are intensive, but at the same time regenerative, must be developed. Aquaculture offers a way in which land can be 'extended' and also regenerated. Fish...